Food Consumption, Developmental Time, and Protein Profile of the Digestive System of the Red Palm Weevil, Rhynchophorus ferrugineus (Coleptera: Dryophthoridae) Larvae Reared on Three Different Diets. Issue 5 (3rd October 2018) - Zulkifli, Ainatun Nadrah; Zakeri, Hazlina Ahamad; Azmi, Wahizatul Afzan
Abstract: The red palm weevil (RPW), Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae) is one of the most dangerous pests of major cultivated palms including coconut, oil palm, and sago. The larval stage of the weevil causes the most destruction of the palms as it completely destroys the palm cabbage. In this study, the larvae were given three different diets—coconut cabbage, oil palm cabbage, and sago stem, under laboratory conditions for food consumption and developmental time experiment. The protein profiles of the digestive systems of the larvae fed on these three diets were also determined. Although the coconut diet was the most consumed by RPW larvae compared to oil palm and sago diets, the growth rate of RPW larvae on oil palm diet was however significantly shorter than those on the coconut and sago diets: the RPW only need 1 mo and 9 d to complete the larval duration. Proteins profiling of eight 2-DE gel protein spots that range 50–20 kDa were identified by mass spectrometry sequence analysis. Based on the Matrix Science Software, the most dominant protein was cationic trypsin. However, based on the NCBI BLAST tool, aminopeptidase N was the most dominant enzyme. This finding can lead to the development of pest control strategies based on the antinutritional protease inhibitors as potential biocontrol agents. Urgent action to find effective control methods should be taken seriously as this weevil is presumed to be one of the serious pests of oil palm industry in Malaysia.